The Effectiveness of The Animated Show Eddy The Clever Fox in Improving The Initial Mathematical Abilities of Children Aged 5-6 Years - Fauziah, Siti Nur; Putra, Yudhitia Nur; Astuti, Wuri (Universitas Negeri Malang, 2024)
In 2018, the results of the Programme For International Student (PISA), indonesia’s mathematics ability had an average score of 379 or ranked 73 out of 79 countries where indonesia’s children were not competent and experienced difficulties in learning related to mathematics. The solution to improve children’s early math skills is to use innovative and interesting learning media for children, namely animation. Therefore, this study aims to find out whether there is a significant difference between before and after the animation of Eddy The Clever Fox in improving the early math skills of children aged 5-6 years. The type of research is quantitative pre-experiment with one group pretest posttest design. Data collection techniques are carried out by testing and documentation. The worksheets are first tested with validity and reliability tests. The mean results in the pretest and posttest were 62.62 and 89.61, which increased after the treatment. The hypothesis test used is the Wilcoxon test with a significance that H₀ is rejected and Hₐ is accepted so that there is a difference between the initial mathematical ability of children aged 5-6 years before and after the treatment in the form of and animated show of Eddy The Clever Fox and it can be concluded that the animation is effective in improving the initial mathematical ability of children aged 5-6 years.